MODERNIZATION OF THE PUBLIC ADMINISTRATION SYSTEM OF UKRAINE IN THE CONTEXT OF EUROPEAN INTEGRATION - Tatarishvili, Shota (Public Management and Policy, 2026)
The article analyzes the theoretical, methodological and institutional principles of modernization of the public administration system of Ukraine in the context of European integration. The purpose of the study is a comprehensive analysis and theoretical justification of the directions of transformation, taking into account the requirements of the EU acquis and the principles of good governance. Modern scientific approaches to understanding reforms are considered, in particular, the concepts of Europeanization, standardization of “good governance” within the SIGMA framework and the digital-era governance paradigm. It is found that these approaches reflect the normative, institutional-evaluative and technological dimensions of transformation and form a holistic model of structural changes. The importance of implementing the principles of good administration enshrined in EU law in the national legal system through the adoption of the Law of Ukraine “On Administrative Procedure” is substantiated, and the role of digitalization as a factor of institutional stability in martial law conditions is proven. The infrastructural elements of the digital state are analyzed, in particular, the interoperability of registers, the functioning of the TREMBITA system, the development of electronic services and the legal regulation of digital documents. It is determined that digital transformation combines improving the quality of services with minimizing corruption risks. Special attention is paid to anti-corruption policy and personnel reform as structural prerequisites for modernization. It is found that the conditionality of EU financial support and the negotiation architecture integrate public administration reform into the external monitoring and evaluation system. It is proven that the effectiveness of the transformation depends on the ability of the “center of government” to ensure institutional policy coherence and the integration of reforms into long-term financial mechanisms. Conclusions are drawn regarding the systemic nature of European integration modernization, which is based on a combination of legal certainty, digital integration, anti-corruption resilience, and professionalization of the civil service.